Aktivitas Ekstrak Biji Tanaman Mindi (Melia azedarach L.) terhadap Spodoptera litura F. (Lepidoptera: Noctuidae) - Hamdani, Hamdani; Supriyatdi, Dedi (Jurnal Agro Industri Perkebunan, 2017)
This study was conducted to evaluate the effectiveness and biological activity of Melia azedarach L. (Meliaceae) seed extract against armyworm, Spodoptera litura F.  The first instar larvae were fed extract-treated broccoli leaves for 2 days, then were maintained on untreated leaves until the third instar stage.  Records were kept in regard to the larvae mortality and developmental time of surviving larvae from the first instar to the third instar. The result showed that M. azedarach L. seed extract at concentration of 50 g.l-1 (5%) exhibited moderate insecticidal activity against S. litura larvae (43,30%-68,33% mortality).  Addition of detergent at 0,2% to extract did not increase insecticidal activity of the extract. However, boiling seed extract at concentration of 50 g.l-1 (5%) during 10 until 20 minutes increased insecticidal activity of extract (66,67%-68,33% mortality).  Generally, M. azedarach seed extract treatment did not affect on developmental time of  S. litura larvae.   Keywords: armyworm, biological activity, botanical insecticide, chinaberry tree, extract